Propuesta para el control de inundaciones mediante tanques de retención de aguas pluviales en Sauces - Cadena Larreta, Luis Eduardo (2025)
This research proposes a solution to the recurring problem of flooding in the Sauces 6 area of Guayaquil, Ecuador. The study will identify factors such as soil impermeability, and drainage system capacity that contribute to the flooding. Based on hydrological data analysis, the project will design and implement modular rainwater retention tanks. The effectiveness of this solution will be evaluated using SWMM software to simulate and compare the performance of the current infrastructure with the expected results of the proposed system. The goal is to mitigate flood risk, enhance stormwater management, and contribute to urban sustainability in Guayaquil.